A Review on Intra-organizational Relations - Alev Özer Torgalöz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This theoretical studyprovides a comprehensive review on intra-organizational relations, with regardto inter-departmental relations, decision-making and conflict. Accordingly, thestudy suggests literature review on intra-organizational power relations,communication and decision making, as these concepts are highly important intoday’s organizational life, organizations consisting of individuals with thenecessity to communicate and balance the relations.